A Study of Agenda-Setting for Local Amalgamation: A Case of Ubon Ratchathani Province - pumkaew, daruneed (King Prajadhipok’s Institute Journal, 2020)
This research is aimed to study the setting of a policy agenda for amalgamation of a large local administrative organization in Ubonratchathani Province. Specifically the merger of the Khamyai Tambon Municipality, Pathum Tambon Municipality, and Rainoi Sub-district Administration. The study uses qualitative methodology with interviews and documentary research. Local administrators, local government staff, are interviewed. The findings showed that local executives were the primary policy entrepreneurs in pushing the merger policy. Public service problems from city’s expansion were used to propel the amalgamation policy. In terms of policy stream, the amalgamation process is clearly supported by law. The steps of merger operation are in accordance with the legally required procedures. The benefits from mergers, such as power to negotiate budgets, is also a key factor in pushing merger onto the policy agenda.